Rapeseed Stand Count Estimation at Leaf Development Stages With UAV Imagery and Convolutional Neural Networks - Zhang, Jian; Zhao, Biquan; Yang, Chenghai; Shi, Yeyin; Liao, Qingxi; Zhou, Guangsheng; Wang, Chufeng; Xie, Tianjin; Jiang, Zhao; Zhang, Dongyan; Yang, Wanneng; Huang, Chenglong; et al. (Frontiers in Plant Science, 2020)
Rapeseed is an important oil crop in China. Timely estimation of rapeseed stand count at early growth stages provides useful information for precision fertilization, irrigation, and yield prediction. Based on the nature of rapeseed, the number of tillering leaves is strongly related to its growth stages. However, no field study has been reported on estimating rapeseed stand count by the number of leaves recognized with convolutional neural networks (CNN) in unmanned aerial vehicle (UAV) imagery. The objectives of this study were to provide a case for rapeseed stand counting with reference to the existing knowledge of the number of leaves per plant, and to determine the optimal timing for counting after rapeseed emergence at leaf development stages with 1 to 7 leaves. A CNN model was developed to recognize leaves in UAV-based imagery and rapeseed stand count was estimated with the number of recognized leaves. The performance of leaf detection was compared using sample sizes of 16, 24, 32, 40 and 48 pixels. Leaf over-counting occurred when a leaf was much bigger than others as this bigger leaf was recognized as several smaller leaves. Results showed CNN-based leaf count achieved the best performance at the 4- to 6-leaf stage with F-scores greater than 90% after calibration with over-counting rate. On average, 806 out of 812 plants were correctly estimated on 53 days after planting (DAP) at the 4- to 6- leaf stage, which was considered as the optimal observation timing. For the 32-pixel patch size, RMSE was 9 plants with rRMSE of 2.22% on 53DAP, while the mean RMSE was 12 with mean rRMSE of 2.89% for all patch size. A sample size of 32 pixels was suggested to be optimal accounting for balancing performance and efficiency. The results of this study confirmed that it was feasible to estimate rapeseed stand count in field automatically, rapidly and accurately. This study provided a special perspective in phenotyping and cultivation management for estimating seedling count for crops that have recognizable leaves at their early growth stage, such as soybean and potato.